Epidemiological trends and patterns of gastric cancer in the Kashmir Valley, India - Shaista Mushtaq; Nisar Ahmad Syed; G.M. Rather; Shahid Saleem; Athar Yousuf Rather; Shaheena Parveen (Clinical Epidemiology and Global Health, 2025)
Aim: To investigate the incidence, demographic characteristics, and distribution of stomach cancer across the Kashmir Valley, with a focus on regional variations. Methods: This study employed a combination of hotspot analysis, spatial clustering, and trend analysis to examine stomach cancer incidence data from 2014 to 2023 across districts in the Kashmir Valley. Data were collected from hospital records, cancer registries, and health databases, encompassing a total of 5554 cases. The study analyzed regional variations in stomach cancer incidence and demographic factors. Hotspot analysis was conducted to identify high-risk areas, while clustering techniques were applied to detect spatial patterns in disease distribution. Trend analysis was performed to assess the changes in stomach cancer cases over the study period. Results: The analysis revealed a significant increase in stomach cancer incidence across all districts of the Kashmir Valley, with the highest rates observed in South Kashmir. Hotspot analysis identified areas with a high concentration of cases in urban areas, particularly in districts such as Anantnag, Pulwama, and Srinagar. Clustering methods highlighted specific regions with persistent high incidence. Trend analysis indicated a steady rise in cases, with a notable peak in 2023. The majority of cases were male, with the highest incidence observed in individuals aged 60–79 years. Conclusion: Stomach cancer incidence in the Kashmir Valley is on the rise, with significant regional variations identified through spatial analysis. The use of hotspot and clustering methods has provided valuable insights into high-risk areas, highlighting the need for targeted public health interventions. Further research into local environmental, dietary, and genetic factors is essential to better understand the increasing burden of stomach cancer in the region.